Intracranial Rosai-Dorfman disease: an infrequent differential diagnosis for meningioma. Report of a case - Castro-Castillo, Elder (2023)
Rosai-Dorfman Disease  is a rare disorder of unknown etiology. Intracranial presentation is even rarer and often mimics the appearance of a meningioma on neuroimaging. Here we present the case of a 38-year-old male patient admitted for an intracranial, extra-axial, supratentorial tumor associated with mild neurological deficit; the presumptive diagnosis was convexity meningioma. After surgery, the definitive histological diagnosis was informed as intracranial Rosai-Dorfman Disease.The differential diagnosis of any extra-axial intracranial lesion suggestive of a meningioma should include intracranial Rosai-Dorfman Disease due to the similarities on clinical presentation and neuroimaging.